A Look at Factors that Impact Growth in Churches of the Evangelical Mennonite Mission Conference - Rempel, Eddy (My University, 2006)
Canadian domination of Christianity is challenged by eastern religions. Affiliation with the Mennonite faith fell 8% from 1991 to 2001 . The Evangelical Mennonite Mission Conference (EMMC) recently adopted a regional structure across Canada, the United States, Mexico, and Belize. It wishes to measure its recent growth rate and investigate growth factors across regions.
Using EMMC Records of church membership and attendance, surveys of senior pastors and church leaders, we grouped the 37 churches by region., size, and growth status, modelled church growth using univariate and multivariable models.
Leaders perception of occupation and activity faith would compromises their faith and the level of assistance their church required and received, and expectation of five-year change in their church attendance were modelled using generalized estimating equations.
Attendance growth varied across regions and church size - small (0-99; 9%), medium (100-299; 14.2%), and large (300+; -3%). For 33 of 37 responding senior pastors 61% of new members were transferees, few churches took listed growth promotion steps, 54% of attendees attend Sunday school, 26% attend Bible study, 30% attended the last annual meeting 42% received a donation receipt, 91% own their building, 70% have the worship space filled less than 80% capacity, 77% had a single board, and 59% had board term limits and the senior pastor overseeing other pastors. None of the tested factors predicted change in attendance.
Almost half (49%) of 517 EMMC registered leaders completed the questionnaire. Of these 87% claimed Mennonite ancestry. The scores measuring the opinionated degree that particular jobs and activities would compromise their faith were higher for leaders with university education, first speaking Plautdietsch, in Mexico or Belize but lower in Saskatchewan. Leaders at new and small churches believe their churches require and received more assistance than those from large churches. The church required assistance score was substantially higher than the received assistance (mean 16.0 vs. 9.4).
In spite of apparent robust growth in the EMMC, this growth is limited to the frontier regions. The demographics of the leaders indicate that outreach to other ethnic groups has not produced leaders yet. We did not identify any factors associated with growth.
Title: A Look at Factors that Impact Growth in Churches of the Evangelical Mennonite Mission Conference, Author: Eddy Rempel, Location: Thode